AutoCAD tutor for engineering graphics : 2013 and beyond - Lang, Kevin (Kevin J.) (Autodesk., 2012)
"A thorough, practical guide featuring self-paced tutorials and a step-by -step approach to help students use and customize AutoCAD to achieve professional results."--Pg.[4] of cover.